PERSEPSI MASYARAKAT TERHADAP POTENSI EKOWISATA DI DESA SEDAHAN JAYA KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - admin, Sri Purnama; M, Iskandar A; Dirhamsyah, M (JURNAL HUTAN LESTARI, 2019)
In the middle ofÂ  rate deforestation, The ecotourism appears as one of alternative economic opportunities for communities around the forest. Sedahan Jaya village is one of the villages in Kayong Utara Regency that has an excellent natural potentials, such as panoramic landscapes, as well as the region's forests and mountains. However, the utilization of natural resources in the village has not been optimally realized. Based on this condition, needed to do research about the perception of Society Against the potential of Â Ecotourism in Sedahan Jaya to know the level of participation and support from the local community. This research uses descriptive survey method that is with interview techniques and tools in the form of a detailed questionnaire form with the number of samples as much as 87 KK. Sampling purposive sampling done by the respondent. The results showed that people in the village of sedahan jaya have a very positive perception against the potential of ecotourism in Sedahan Jaya village following its development. This is because most of the people in the village of sedahan jaya has felt the positive impact of this ecotourism activities to their lives, both in terms of the economy as well as socio-cultural area.Keywords : ecotoutism, public perception, Sedahan Jaya.